Prevalence of dementia syndromes in older adults in a community - Mesa Trujillo, Daisy; García Mesa, Israel; Rodríguez Núñez, Sonia (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: the increase in longevity and survival has led to an increase in the prevalence of diseases in advanced ages; dementia is today one of the main causes of disability and dependence among older adults with a physical, psychological, social and economic impact not only on those who suffer from it, but also on their caregivers, family and society.Objective: to estimate the prevalence of dementia syndrome in adults aged 65 and over, belonging to the medical office No.1 of Los Palacios municipality, Pinar del Río province, in 2019.Methods: a cross-sectional descriptive observational study was conducted. Universe, coincided with the sample of 150 older adults who met the inclusion criteria. Theoretical and empirical methods were applied, such as the instruments developed by the Dementia Research Group 10/66 and descriptive statistics.Results: adults aged 80 years and older, female, illiterate, without a partner, from rural areas predominated; within the lifestyles and vascular risk factors, risk drinkers, physical inactivity, smoking; history of stroke, cranial trauma and arterial hypertension; as for mental health, depression, anxiety, and feelings of loneliness; in the neuropsychological variables, alterations in semantic memory.Conclusions: the prevalence of dementia syndrome is notable in older adults, which shows that it constitutes an important health problem.